Indication that the behavioural responses of humpback whales to killer whale sounds are influenced by trophic relationships - Benti, Benjamin; Miller, Patrick J. O.; Biuw, Martin; Curé, Charlotte (Marine Ecology Progress Series, 2021)
International audience Eavesdropping, the detection of communication signals by unintended receivers, can be beneficial in predator-prey interactions, competition, and cooperation. The cosmopolitan killer whale Orcinus orca has diverged into several ecotypes which exhibit specialised diets and different vocal behaviours. These ecotypes have diverse ecological relationships with other marine mammal species, and sound could be a reliable sensory modality for eavesdroppers to discriminate between ecotypes and thereby respond adaptively. Here, we tested whether humpback whales Megaptera novaeangliae in the Northeast Atlantic responded differently to playback of the sounds of 2 killer whale ecotypes, Northeast Atlantic herring-feeding killer whales representing food competitors and Northeast Pacific mammal-eating killer whales simulating potential predators. We used animal-borne tags and surface visual observations to monitor the behaviour of humpback whales throughout the playback experiments. Humpback whales clearly approached the source of herring-feeding killer whale sounds (5 of 6 cases), suggesting a ‘dinner-bell’ attraction effect. Responses to mammal-eating killer whale sounds varied with the context of presentation: playback elicited strong avoidance responses by humpback whales in offshore waters during summer (7 of 8 cases), whereas the whales either approached (2 of 4 cases) or avoided (2 of 4 cases) the sound source in inshore waters during winter. These results indicate that humpback whales may be able to functionally discriminate between the sounds of different killer whale ecotypes. Acoustic discrimination of heterospecific sounds may be widespread among marine mammals, suggesting that marine mammals could rely on eavesdropping as a primary source of information to make decisions during heterospecific encounters.